2010
DOI: 10.2109/jcersj2.118.66
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic alignment of non-modified BN nanosheets in polysiloxane matrix under nano pulse width electricity

Abstract: Boron nitride (BN) nanosheets/polysiloxane composites were fabricated under nano pulse width electric field to enhance the anisotropic alignment of BN nanosheets in a viscous matrix. BN nanosheets have unique physical and thermal properties and exhibit semiconducting behavior with a wide band gap comparing to carbon graphite. However the researches over one dimensional arrangement of BN nanosheets with application of the electric field are limited. The difficulty of modifying the BN surface with electrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The morphological characteristics of these nanosheets are described elsewhere [28]. A PVDF (molecular weight av = ~534,000) from Sigma-Aldrich Co. is used as a polymer matrix.…”
Section: Methodsmentioning
confidence: 99%
“…The morphological characteristics of these nanosheets are described elsewhere [28]. A PVDF (molecular weight av = ~534,000) from Sigma-Aldrich Co. is used as a polymer matrix.…”
Section: Methodsmentioning
confidence: 99%
“…15 In particular, nanosheets are susceptible to higher reversing forces, such as viscoelasticity and shear forces, which is stronger than those encountered by one-dimensional fillers, such as nanorods, nanofibers, or nanotubes. 12 Figure 2 shows SEM and TEM micrographs of hexagonal BN nanosheets with average diameters (D 90 ) of 10.6 lm and an average aspect ratio of 141.3. 12 Figure 2 shows SEM and TEM micrographs of hexagonal BN nanosheets with average diameters (D 90 ) of 10.6 lm and an average aspect ratio of 141.3.…”
Section: (1) Orientation and Formation Of Linear Bundle Structure Of mentioning
confidence: 99%
“…The alignment of nanosheets via reorientation in a polymer is a critical technique, and shear forces, 8 magnetic forces, 9 and electric fields 10 have been widely used to reorient nanosheets in a polymer matrix. 11 In our earlier work, unmodified BN nanosheets were incorporated into polysiloxane with the desired orientation, 12 and fabrication of linear assemblies of BN nanosheets (LABNs) were introduced under a dc electric field; the stretched structure induced effective heat emission through the out-of-plane direction of the composite film. In the orientation of nanosheets using magnetic forces, the nanosheet surface must be modified by metallic nanopowders, such as iron nanoparticles, for better orientation of the nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the intensity of the electric field that can be applied to the composite system is limited by electrical breakdown and burnout of the material caused by application of an electric field intensity higher than the breakdown voltage. 15) We recently reported that a nanosecond pulse electric field does not cause electrical breakdown, yet orients insulating BN nanosheets: 15), 16) electrical breakdown caused by application of 1 kV DC did not occur when up to a 40 kV nanosecond pulse electric field was applied. The anisotropic orientation of the BN nanosheets was demonstrated by activating the diamagnetic susceptibility of the c-axis of the BN using a high (10 T) magnetic field.…”
Section: Introductionmentioning
confidence: 99%